2015
DOI: 10.1007/s12529-015-9485-z
|View full text |Cite
|
Sign up to set email alerts
|

Stages of Change for Voluntary Medical Male Circumcision and Sexual Risk Behavior in Uncircumcised Zambian Men: The Spear and Shield Project

Abstract: Background Dissemination and scale up of voluntary medical male circumcision (VMMC) programs is well supported by evidence that VMMC reduces HIV risk in populations with high HIV prevalence and low rates of circumcision, as is the case in Zambia. Purpose At both individual and population levels, it is important to understand what stages of change for VMMC are associated with, especially across cultures. This study evaluated VMMC knowledge, misinformation and stages of change for VMMC of uncircumcised men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…In Zambia, especially in the Copperbelt and Lusaka provinces, and in Swaziland, the contribution of never married men was very high, a finding that is partly explained by the low prevalence of circumcision in these countries [ 52 ]. Findings from studies investigating the determinants of uptake of voluntary medical male circumcision in these two countries should inform its scale up [ 53 56 ], and strategies such as early infant circumcision [ 57 , 58 ] or circumcision among adolescents through school programmes [ 59 ], which are likely to have higher acceptability, should be promoted [ 60 ]. Never married women were also disproportionately affected in Swaziland compared to their population size (see S2 Fig ), and similarly in Zambia, Gabon, the Southern province in Malawi, and Kigali City and the South province in Rwanda.…”
Section: Discussionmentioning
confidence: 99%
“…In Zambia, especially in the Copperbelt and Lusaka provinces, and in Swaziland, the contribution of never married men was very high, a finding that is partly explained by the low prevalence of circumcision in these countries [ 52 ]. Findings from studies investigating the determinants of uptake of voluntary medical male circumcision in these two countries should inform its scale up [ 53 56 ], and strategies such as early infant circumcision [ 57 , 58 ] or circumcision among adolescents through school programmes [ 59 ], which are likely to have higher acceptability, should be promoted [ 60 ]. Never married women were also disproportionately affected in Swaziland compared to their population size (see S2 Fig ), and similarly in Zambia, Gabon, the Southern province in Malawi, and Kigali City and the South province in Rwanda.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome measure for the study was VMMC uptake; of the 800 men enrolled, 257 men (experimental condition, n = 161; control condition, n = 96) underwent VMMC during the course of the study. 19 , 22 Secondary outcomes included maintenance of sexual barrier use following VMMC, 19 the acceptability of VMMC, 22 female partner influence on VMMC uptake, 13 and sexual satisfaction following VMMC. The analysis in this article focuses on sexual satisfaction and post-VMMC experiences of the 257 male study participants who underwent VMMC and the 159 female partners who completed post-VMMC questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2012 review, the American Academy of Pediatrics concluded that health benefits of newborn circumcision not only outweigh the risks, but also justify being accessible to all families that choose this option [ 48 ]. Long-term benefits include the prevention of HPV transmission (as a precursor to cervical cancer among adult women) as well as a reduction in risk for UTIs, HIV, and penile cancer [ 50 ]. A more immediate benefit includes an improvement in hygiene [ 15 ].…”
Section: Discussionmentioning
confidence: 99%